2022
DOI: 10.1111/gcb.16272
|View full text |Cite
|
Sign up to set email alerts
|

Realistic rates of nitrogen addition increase carbon flux rates but do not change soil carbon stocks in a temperate grassland

Abstract: Soils store 2.5 and plants store 1.5 times as much C compared to the atmosphere, respectively (Schlesinger & Bernhardt, 2013). Thus, even small changes to the size of these C sinks, or to rates of photosynthesis or respiration, could have large consequences for atmospheric CO 2 levels. Importantly, other global change drivers, such as nitrogen (N) deposition (Stevens, 2019;Vitousek et al., 1997), may be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…Elevated CO 2 generally stimulates plant growth and vegetation productivity, at least in the absence of strong nutrient limitation (Ainsworth & Long, 2005; de Graaff et al, 2006; Norby et al, 2010), but the increase in plant biomass does not always lead to soil C stock accumulation (van Groenigen et al, 2014), which is contingent on the trade‐off between plant biomass and soil C storage (Terrer et al, 2021). Other global change factors such as N addition and altered precipitation likewise profoundly affect the C pools and fluxes (Liu & Greaver, 2010; Lu et al, 2021; Nielsen & Ball, 2015; Wilcots et al, 2022; Wu et al, 2011; Zheng et al, 2022). These multiple global changes influence the C and nutrient cycling to a greater or lesser extent through soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated CO 2 generally stimulates plant growth and vegetation productivity, at least in the absence of strong nutrient limitation (Ainsworth & Long, 2005; de Graaff et al, 2006; Norby et al, 2010), but the increase in plant biomass does not always lead to soil C stock accumulation (van Groenigen et al, 2014), which is contingent on the trade‐off between plant biomass and soil C storage (Terrer et al, 2021). Other global change factors such as N addition and altered precipitation likewise profoundly affect the C pools and fluxes (Liu & Greaver, 2010; Lu et al, 2021; Nielsen & Ball, 2015; Wilcots et al, 2022; Wu et al, 2011; Zheng et al, 2022). These multiple global changes influence the C and nutrient cycling to a greater or lesser extent through soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of low-N addition (5 g m −2 yr −1 ) on most optical and molecular characteristics of soil DOM were inconsistent with those of medium-and high-N addition (10 and 15 g m −2 yr −1 ), indicating that N addition rate was an important moderator. A recent study also reported that realistic rates of N addition differently influence soil C flux rates and C stocks (Wiclots et al 2022). The reason for no significant effects of low-N addition on these characteristics of soil DOM might be associated with no change in soil acidification status and SOC pool under low-N addition.…”
Section: Discussionmentioning
confidence: 93%
“…Alterations in molecular-level information with N addition were probably due to N-induced differences in both soil properties and microbial activities as compared to control plots (Averill and Waring 2018, Li et al 2019, Wiclots et al 2022.…”
Section: Discussionmentioning
confidence: 99%
“…were not changed by nitrogen addition alone (Harpole et al, 2007;Wilcots et al, 2022). Harpole et al (2007) and Wilcots et al (2022) only added nitrogen while we added nitrogen, phosphorus, potassium and micronutrients.…”
Section: Seasonal Variation In Nutrient and Consumer Impacts On C Flu...mentioning
confidence: 97%
“…were not changed by nitrogen addition alone (Harpole et al, 2007;Wilcots et al, 2022). Harpole et al (2007) and Wilcots et al (2022) only added nitrogen while we added nitrogen, phosphorus, potassium and micronutrients. The contrasting results between our work and these previous studies for both NEE and above-ground biomass suggest nutrient colimitation not only for plant productivity but also for ecosystem C fluxes (Fay et al, 2015;Harpole et al, 2011).…”
Section: Seasonal Variation In Nutrient and Consumer Impacts On C Flu...mentioning
confidence: 97%